Improving students’ Entreprenneurial skills – a cross-border experience - Anurak, Binnui; Syaharom, Abdullah (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.